(untitled) (Medicine Today, 2023)
Introduction: Epilepsy is a common, chronic and non-communicable disorder of the brain. Carbamazepine, increasing serum cholesterol level, causes adverse cardiovascular and cerebrovascular events. Sodium valproate causes weight gain, hyperinsulinemia and insulin resistance leading to metabolic syndrome. These all causes increased morbidity and mortality of epileptic patients in later life. Objective: to find out the effects of carbamazepine and sodium valproate on serum cholesterol in epileptic patients. Materials and Methods: This cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College during the period of July 2017 to June 2018. A total of sixty diagnosed epileptic patients were selected, of them, thirty patients were taking carbamazepine and thirty on sodium valproate. Data were analyzed with the help of SPSS version 22.0. Unpaired Student’s t-test and Mann-Whitney U test were done to see the level of significance (p<0.05). For correlation, Pearson’s correlation coefficient test was done. Result: Mean ± SD of serum total cholesterol in carbamazepine and sodium valproate patients were 218.73 ± 29.70 mg/dl and 190.14 ± 17.10 mg/dl respectively (p<0.001). Conclusion: This study reveals that hypercholesterolemia is related to carbamazepine medications. Medicine Today 2023 Vol.35(2): 83-86